MANAGEMENTUL INOVAȚIONAL: (STUDIU DE CAZ: BIBLIOTECA ȘTIINȚIFICĂ A USARB) - LUCHIANCIUC, Biblioteca Științifică, Universitatea de Stat „Alecu Russo”, Bălți, Natalia (BIBLIOPOLIS, 2020)
Abstract This extract of the tesis of Natalia Luchianciuc is about the innovative management, a theme required for of all libraries types. Through a case study the author identifies innovative management elements of BS USARB activity, exemplifying with results and their practical application. The case study reveals that BS USARB is an innovative library, the librarians BS USARB are innovators. The empirical results confirm the assumption that BS USARB is an innovative library.